Nanomedicine-based drug targeting for psoriasis: potentials and emerging trends in nanoscale pharmacotherapy. (April 2015) - Rahman, Mahfoozur; Akhter, Sohail; Ahmad, Javed; Ahmad, Mohammad Zaki; Beg, Sarwar; Ahmad, Farhan Jalees
<x xml:space="preserve">Abstract</x> Introduction: Psoriasis is a T-cell mediated autoimmune inflammatory skin disease recognized by skin surface inflammation, epidermal proliferation, hyperkeratosis, angiogenesis and anomalous keratinization. Currently, various pharmacotherapies are available for it; however, pharmacotherapy based on conventional formulations can provide therapeutic benefits only to a limited extent. Recent advancement in nanotechnology-based nanomedicines has led to the possibility of improving the efficacy and safety of pharmacotherapeutic agents for psoriasis. Areas covered: This review covers the brief pathophysiology of psoriasis, available medications and its associated challenges in treatment. Collective accounts of various drugs acting on different molecular targets of psoriasis and the role of nanomedicines in their effective targeting are discussed. Moreover, newer approaches in psoriatic therapy such as combination drug targeting and physical techniques of topical permeation enhancement along with nanomedicines are also discussed. Expert opinion: Novel nanomedicines (such as liposomes, polymeric nanoparticles, etc.) have shown their potential in improving therapeutic benefits of antipsoriatic drugs by increasing their therapeutic efficacy with minimal toxicity. Nevertheless, while the results on animal models using nanomedicine-based drug targeting of psoriasis via different route seem promising, lack of sufficient evidence in a clinical setup is a constraint and more clinical studies on the efficacy and safety of nanomedicines in psoriasis therapy are required.